THE EFFECT OF METFORMIN ON THYROID PROFILE IN PATIENTS WITH POLYCYSTIC OVARIAN SYNDROME AND SUBCLINICAL HYPOTHYROIDISM - T.NIVETHITHA,; S.VIJAYALAKSHMI, (International Journal of Pharma and Bio Sciences, 2015)
Polycystic ovarian syndrome and hypothyroidism are closely associated. Metformin is routinely prescribed for the treatment and has proven clinical and biological benefits. Hence this study was conducted to assess the effect of Metformin on thyroid profile in patients with polycystic ovarian syndrome and subclinical hypothyroidism, who were diagnosed according to Rotterdam’s criteria. 64 patients were taken for the final analysis. Apart from and significant reductions in body weight, body mass index, Metformin caused a significant reduction in serum Thyroid stimulating hormone (TSH) from 8.24±0.63µIU/ml to 2.67±0.29µIU/ml (P < 0.001). Thus, from this study we conclude that Metformin can be used either as a sole therapy or as an adjuvant in women with Polycystic ovarian syndrome and subclinical hypothyroidism and clinical hypothyroidism, respectively.